Large-Scale Protein and Phosphoprotein Profiling to Explore Potato Resistance Mechanisms to Spongospora subterranea Infection - Balotf, Sadegh; Wilson, Calum R.; Tegg, Robert S.; Nichols, David S.; Wilson, Richard (Frontiers in Plant Science, 2022)
Potato is one of the most important food crops for human consumption. The soilborne pathogen Spongospora subterranea infects potato roots and tubers, resulting in considerable economic losses from diminished tuber yields and quality. A comprehensive understanding of how potato plants respond to S. subterranea infection is essential for the development of pathogen-resistant crops. Here, we employed label-free proteomics and phosphoproteomics to quantify systemically expressed protein-level responses to S. subterranea root infection in potato foliage of the susceptible and resistant potato cultivars. A total of 2,669 proteins and 1,498 phosphoproteins were quantified in the leaf samples of the different treatment groups. Following statistical analysis of the proteomic data, we identified oxidoreductase activity, electron transfer, and photosynthesis as significant processes that differentially changed upon root infection specifically in the resistant cultivar and not in the susceptible cultivar. The phosphoproteomics results indicated increased activity of signal transduction and defense response functions in the resistant cultivar. In contrast, the majority of increased phosphoproteins in the susceptible cultivar were related to transporter activity and sub-cellular localization. This study provides new insight into the molecular mechanisms and systemic signals involved in potato resistance to S. subterranea infection and has identified new roles for protein phosphorylation in the regulation of potato immune response.